Interhemispheric Brain Communication and the Evolution of Turn-Taking in Mammals - Ravignani, Andrea; Lumaca, Massimo; Kotz, Sonja A. (Frontiers in Ecology and Evolution, 2022)
In the last 20 years, research on turn-taking and duetting has flourished in at least three, historically separate disciplines: animal behavior, language, and music cognition. While different in scope and methods, all three ultimately share one goal - namely the understanding of timed interactions among conspecifics. In this perspective, we aim at connecting turn-taking and duetting across species from a neural perspective. While we are still far from a defined neuroethology of turn-taking, we argue that the human neuroscience of turn-taking and duetting can inform animal bioacoustics. For this, we focus on a particular concept, interhemispheric connectivity, and its main white-matter substrate, the corpus callosum. We provide an overview of the role of corpus callosum in human neuroscience and interactive music and speech. We hypothesize its mechanistic connection to turn-taking and duetting in our species, and a potential translational link to mammalian research. We conclude by illustrating empirical venues for neuroethological research of turn-taking and duetting in mammals.